The Effect of Influencer Marketing on Consumer Behavior of Fashion Style in the Age of Social Media - Khoirun Nissa; Priyanshi Chauhan; Mohamed Asim; Princy Chaudhary; Dwi Nita Aryani; Koay Loke Kean; Anurag Hazarika (AIBPM Publisher, 2024)
This study aims to explore the effect of influencer marketing on consumer behavior regarding fashion styles in the age of social media. It employs a quantitative research approach utilizing simple linear regression analysis conducted with SPSS. The data for this study were collected through primary sources via questionnaires distributed in two countries, Indonesia and India, to ensure a comprehensive understanding of the phenomenon. A total of 55 respondents from Indonesia and 50 respondents from India participated in the study. The results indicate that influencer marketing has a significant positive effect on consumer behavior. The benefits of this study are expected to assist the fashion industry in understanding consumer behavior and the role of influencers, ultimately improving their marketing strategies. However, the findings do not lead to general conclusions due to the limited number of respondents and other factors that can influence consumer behavior. For future research, it is recommended to increase the sample size and expand the scope of the discussion by incorporating additional aspects such as pricing and the aesthetics of content